2014
DOI: 10.1584/jpestics.d14-006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of <i>Aspergillus clavatus</i> produced in a fungal biofilm bioreactor toward <i>Culex quinquefasciatus</i> (Diptera: Culicidae)

Abstract: Many entomopathogenic fungi have been demonstrated to be potential agents for efficiently controlling mosquito populations. In the present study, we investigated a bioreactor system to produce metabolites and conidia by combining technological advantages of submerged and solid-state fermentations. The efficiency of fungal products was tested toward mosquitoes. Aspergillus clavatus (Eurotiales: Trichocomaceae) was grown by semi-solid-state fermentation in a bioreactor for up to 7 days. Depending on conidial dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The three fungi species were confirmed to be entomopathogenic fungi and not plants pathogens. This is in accordance with the finding of Thomsen et al (2001), Barta and Cagáň (2006), Seye et al (2014), Zhang et al (2015), Frisvad et al (2019), da Silva Santos (2020), de H. C. Maciel et al (2021), andFitriana et al (2021).…”
Section: Identification Of Entomopathogenic Fungisupporting
confidence: 93%
See 1 more Smart Citation
“…The three fungi species were confirmed to be entomopathogenic fungi and not plants pathogens. This is in accordance with the finding of Thomsen et al (2001), Barta and Cagáň (2006), Seye et al (2014), Zhang et al (2015), Frisvad et al (2019), da Silva Santos (2020), de H. C. Maciel et al (2021), andFitriana et al (2021).…”
Section: Identification Of Entomopathogenic Fungisupporting
confidence: 93%
“…Two hypotheses were proposed regarding the physical mechanisms of Aspergillus, namely, (1) mycelium grows after direct contact on the insect cuticle or (2) mycelium grows and reproduces into the insect intestine after eaten by insects. The latter is consistent with the mechanism of Hypocreales (Seye et al, 2014). In addition to the physical mode of action, some Aspergillus, such as A. flavus, produce lytic enzymes and secondary metabolites.…”
Section: Identification Of Entomopathogenic Fungisupporting
confidence: 84%
“…Biofilm reactors are a fermentation system for the production of value-added products that combine SmF and SSF approaches, where the biomass adheres to an inert support [28]. In this sense, the availability of oxygen in the solid fermentation (gaseous phase) will be exploited even when there is oxygen saturation in the liquid phase.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported goods yields in protein production (hydrophobin II) by Trichoderma reesei [20]. In addition, conidia and secondary metabolites produced by Aspergillus clavatus in a biofilm reactor have been shown to be effective in mosquito (Culex quinquefasciatus) control [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since cell adhesion may play a fundamental role in biofilm development, new approaches for materials serving as inert surfaces for producing filamentous fungi are necessary. Semisolid‐state fermentation (semi–SSF), a SSF modification based on the surface‐adhesion principle, is an alternative for producing fungal conidia in engineered systems (Musoni et al, 2015; Seye et al, 2014). Some studies highlighted that this fermentation approach enables considerable yields in terms of fungal biomass and metabolites such enzymes (Higuchi et al, 1997; Jenkins & Lomer, 1994; Kumar & Singh, 2001; Osma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%